1994
DOI: 10.1111/j.1439-0426.1994.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield estimates, catch, effort and fishery potential of the reef flat in Cape Bolinao, Philippines

Abstract: Catch, fishing effort and yield estimates of the Cape Bolinao reef flat fishery in Lingayen Gulf, Philippines are provided, based on data collected from Ma 1987 to April 1988. The dynamics of the a high rofuction in s ite of heavy fishin pressure. However, yield comparisons with those of other reef fisgeries in the Inlo-Pacific region, akng with characteristics of the catch and the use of multiple gear types, suggest that current extraction rates should not be increased. dominants ecies, the rabbitfish Siganus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Likewise, significant population genetic structure along the eastern Philippine seaboard (Magsino and JuinioMeñez 2008), and among three major marine basin regions, i.e., South China Sea, northeast Philippine Sea, and southeast Philippine Sea-Sulu-Celebes Seas, indicate these should be considered as distinct regional management units (Ravago-Gotanco and Juinio-Meñez 2010). Across smaller spatial scales, analyses of mtDNA sequences and microsatellite data detect significant genetic structure across the western Luzon coast, relevant in particular for S. fuscescens populations in Bolinao, a significant fishery characterized by high levels of exploitation over many decades (Campos et al 1994). Assignment-based analyses of multilocus genotypes indicate asymmetric patterns of gene flow; populations in the Lingayen Gulf are self-recruiting, and serve as the source population for reefs located farther south along the western Luzon coast (Ravago-Gotanco 2010).…”
Section: Genetic Structure Of Philippine Populations Of Siganus Fuscementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, significant population genetic structure along the eastern Philippine seaboard (Magsino and JuinioMeñez 2008), and among three major marine basin regions, i.e., South China Sea, northeast Philippine Sea, and southeast Philippine Sea-Sulu-Celebes Seas, indicate these should be considered as distinct regional management units (Ravago-Gotanco and Juinio-Meñez 2010). Across smaller spatial scales, analyses of mtDNA sequences and microsatellite data detect significant genetic structure across the western Luzon coast, relevant in particular for S. fuscescens populations in Bolinao, a significant fishery characterized by high levels of exploitation over many decades (Campos et al 1994). Assignment-based analyses of multilocus genotypes indicate asymmetric patterns of gene flow; populations in the Lingayen Gulf are self-recruiting, and serve as the source population for reefs located farther south along the western Luzon coast (Ravago-Gotanco 2010).…”
Section: Genetic Structure Of Philippine Populations Of Siganus Fuscementioning
confidence: 99%
“…Of the estimated 15 rabbitfish species which occur across the Philippine archipelago, the mottled spinefoot, Siganus fuscescens, is considered the most exploited, with evidence of overfishing (Jumawan-Nanual andMetillo 2008, Soliman et al 2009). Widely-distributed in reef flats and seagrass meadows, the species is harvested throughout most of its life cycle: presettlement juveniles are collected as they arrive in dense schools to settle on the reef flat, and juvenile and adult stages are fished year round (Campos et al 1994). Relatively much is known about the biology and ecology of the mottled spinefoot (e.g., Alcala et al 1979, de la Paz and Aragones 1990, Woodland 1990, although some confusion still exists in distinguishing the species from its morphologically similar sibling species, Siganus canaliculatus.…”
Section: Genetic Structure Of Philippine Populations Of Siganus Fuscementioning
confidence: 99%
“…At the beginning they may tend to resist recruitment overfishing (Cushing, 1972) but high exploitation of its spawning stock exacerbates the problem. This could be a reason for the observation that S. fuscescens may have been resilient to high exploitation in Lingayen Gulf, Philippines (see Campos et al., 1994). But the 4‐year data of the present study showed evident continuous juvenile catch decline as not mainly due to inter‐annual recruitment variability and climatic oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…The species is a highly-exploited, commercially valuable resource throughout the Philippine archipelago, with mounting evidence of overfishing (Campos et al 1994;Jumawan-Nanual and Metilla 2008;Soliman et al 2009). Exploitation occurs throughout most of the species' life cycle, as early as the presettlement stage when the fish arrive in dense schools to settle on the reef flat, continuing through the juvenile and adult stages which are fished yearround (Campos et al 1994).…”
mentioning
confidence: 96%
“…The species is a highly-exploited, commercially valuable resource throughout the Philippine archipelago, with mounting evidence of overfishing (Campos et al 1994;Jumawan-Nanual and Metilla 2008;Soliman et al 2009). Exploitation occurs throughout most of the species' life cycle, as early as the presettlement stage when the fish arrive in dense schools to settle on the reef flat, continuing through the juvenile and adult stages which are fished yearround (Campos et al 1994). Genetic approaches to estimating the patterns and spatial scales of dispersal and connectivity can contribute to an understanding of the dynamics of populations, their resilience to disturbance, and provide important information to guide management efforts (Jones et al 2009).…”
mentioning
confidence: 96%